Bahasa Inggris - Safitri, Prahesti Tirta; Raharjo, Sigit; Kuncara, Faatihah Nanda (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Nowadays, technology is developing rapidly. Augmented reality is one of the technologies frequently used in the learning process. The purpose of augmented reality-based learning is to improve mathematical reasoning skills by providing interesting and appropriate learning media. This study aims to develop mathematics learning media for flat-sided spatial geometry material based on augmented reality that can be tested on grade VII students of SMPN 16 Tangerang City. This research uses the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The research data includes both qualitative and quantitative data. The instruments used are media validity expert assessments, media practitioner assessments, and respondent responses. The results of the study showed a significant increase in students' knowledge and skills during the learning process of mathematics on cube and cuboid materials based on augmented reality in grade VII students of SMPN 16 Tangerang City. This is indicated by the expert assessment results, which rated it as